Toulouse) Femme au piaNo - Théodule Ribot - Oxford. The Ashmolean... - Didier Descouens (Wikimedia Commons, 2021)
Notice iconographique issue de Wikimedia Commons. Titre: (Toulouse) Femme au piaNo - Théodule Ribot - Oxford. The Ashmolean Museum of Art and Archeology UK.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures